Efficient Green Light Acclimation of the Green Algae Picochlorum sp. Triggering Geranylgeranylated Chlorophylls - Paper, Michael; Glemser, Matthias; Haack, Martina; Lorenzen, Jan; Mehlmer, Norbert; Fuchs, Tobias; Schenk, Gerhard; Garbe, Daniel; Weuster-Botz, Dirk; Eisenreich, Wolfgang; Lakatos, Michael; Brück, Thomas B. (Frontiers in Bioengineering and Biotechnology, 2022)
In analogy to higher plants, eukaryotic microalgae are thought to be incapable of utilizing green light for growth, due to the “green gap” in the absorbance profiles of their photosynthetic pigments. This study demonstrates, that the marine chlorophyte Picochlorum sp. is able to grow efficiently under green light emitting diode (LED) illumination. Picochlorum sp. growth and pigment profiles under blue, red, green and white LED illumination (light intensity: 50 – 200 µmol m-2 s-1) in bottom-lightened shake flask cultures were evaluated. Green light-treated cultures showed a prolonged initial growth lag phase of one to two days, which was subsequently compensated to obtain comparable biomass yields to red and white light controls (approx. 0.8 gDW L-1). Interestingly, growth and final biomass yields of the green light-treated sample were higher than under blue light with equivalent illumination energies. Further, pigment analysis indicated, that during green light illumination, Picochlorum sp. formed unknown pigments (X1-X4). Pigment concentrations increased with illumination intensity and were most abundant during the exponential growth phase. Mass spectrometry and nuclear magnetic resonance data indicated, that pigments X1-X2 and X3-X4 are derivatives of chlorophyll b and a, which harbor C=C bonds in the phytol side chain similar to geranylgeranylated chlorophylls. Thus, for the first time, the natural accumulation of large pools (approx. 12 mg gDW-1) of chlorophyll intermediates with incomplete hydrogenation of their phytyl chains is demonstrated for algae under monochromatic green light (Peak λ 510 nm, full width at half maximum 91 nm). The ability to utilize green light offers competitive advantages for enhancing biomass production, particularly under conditions of dense cultures, long light pathways and high light intensity. Green light acclimation for an eukaryotic microalgae in conjunction with the formation of new aberrant geranylgeranylated chlorophylls and high efficiency of growth rates are novel for eukaryotic microalgae. Illumination with green light could enhance productivity in industrial processes and trigger the formation of new metabolites– thus, underlying mechanisms require further investigation.